Extramedullary Hematopoiesis Mimicking Mediastinal Tumor in a Patient with Hereditary Spherocytosis: Case report. (2017) - Park, Jae Bum; Lee, Song Am; Kim, Yo Han; Lee, Woo Surng; Hwang, Jae Joon
Highlights: Extramedullary hematopoiesis may occur as mimicking intrathoracic mediastinal tumor. Surgical diagnostic confirmation should be considered in conjunction with radiology and clinical judgment. EMH mimicking mediastinal tumor mass is required to obtain exact histological diagnosis and secure resection. Video-assisted thoracoscopic surgery (VATS) is amendable and less invasive alternative for the definite diagnosis as well as surgical removal. Abstract: Introduction: Extramedullary hematopoiesis (EMH) is a rare disorder, defined as the appearance of hematopoietic elements outside the bone marrow or peripheral blood. The exact mechanism of this development is still unknown. We herein report a case of intrathoracic EMH, manifesting as a posterior mediastinal tumor in a patient with hereditary spherocytosis. Presentation of case: A 45-year-old man who presented with anemia, jaundice and abdominal pain was diagnosed with hereditary spherocytosis. A 2.6 cm homogeneous right paravertebral (at the level of T8) round mass of soft tissue density was discovered incidentally on computed tomography. We performed a complete excision of mass lesion by video-assisted thoracoscopic surgery (VATS) to confirm the diagnosis. It appeared to be well encapsulated and contained bloody, fragile material. A pathological result disclosed a normal diffuse hematopoiesis consisting of megakaryocytes, immature granulocytic and myeloid precursor cells, and finally confirmed a diagnosis of EMH. Furthermore, laparoscopic splenectomy and cholecystectomy surgery was accomplished uneventfully as well. Discussion: It was very significant to differentiate posterior mediastinal neurogenic tumor from EMH, as it can be clinically confused with other tumors of the mediastinum. Radiological examination has limitations, so definite diagnostic confirmation by surgical approach should be considered. Conclusion: We successfully performed a complete removal of intrathoracic mediastinal mass and confirmed a diagnosis of extramedullary hematopoiesis (EMH) which is mimicking mediastinal neoplasm.